Antimicrobial resistance genes in pigeons from public parks in Costa Rica - Blanco Pena, K. (2017)
Antimicrobial resistance is known to be an emerging problem, but the extent of the issue remains incomplete. The aim of this study was to determine the pres- ence or absence of nine resistance genes (blaTEM, catI, mecA, qnrS, sulI, sulII, tet (A), tet(Q), vanA) in the faeces of 141 pigeons from four urban parks in Alajuela, Guadalupe, Tres Rıos and San Jose in Costa Rica. The genes were identified by real-time PCR directly from enema samples. About 30% of the samples were pos- itive for genes catI and sulI; between 13% and 17% were positive for qnrS, sulII, tet(A) and tet(Q); and 4% were positive for blaTEM. The mecA and vanA genes were not detected. The average of antimicrobial resistance genes detected per pigeon was 2. Eight different patterns of resistance were identified, without differ- ences in the sampling areas, being the most common pattern 2 (sulII positive samples). During rainy season, the genes more frequently found were sulI and tet (A). In conclusion, the urban inhabiting pigeons tested are currently carrying antimicrobial resistance genes, potentially acting as reservoirs of resistant bacteria and vectors to humans. To the authors’ knowledge, this is the first study carried out on direct detection of resistance genes in the digestive metagenomes of pigeons.